International Financial Reporting Standards Implementation : a Global Experience - Nurunnabi, Mohammad (Contributions to International Accounting, 2021)
Contributions to International Accountingaims to address a vital gap in research by focusing on providing relevant and timely studies on International Financial Reporting Standards implementation for local and international policymakers.